High expression of circulating exosomal circAKT3 is associated with higher recurrence in HCC patients undergoing surgical treatment. (June 2020) - Luo, Yanwei; Liu, Fengxia; Gui, Rong
Abstract: Exosome-enriched circular RNAs (circRNAs) have become new biomarkers of cancers. In this study, we examined the expression of exosomal circAKT3 and analyzed its association with clinicopathological features and prognosis of patients with hepatocellular carcinoma (HCC). CircAKT3 levels from circulating exosomes in 124 patients with HCC and 100 healthy subjects were measured by quantitative polymerase chain reaction. We defined higher circulating exosomal circAKT3 as > 1‐fold that of the healthy subjects. The expression of exosomal circAKT3 in HCC patients was significantly increased compared with healthy subjects. Patients with high circulating exosomal circAKT3 had higher tumor recurrence rates (hazard risk (HR), 3.14; 95% confidence interval (CI), 1.29–6.21, P = 0.012) and higher mortality (HR, 1.89; 95% CI, 1.04–3.01), P = 0.048). Survival analysis showed that the overall survival rate and recurrence-free survival rate of patients with high exosomal circAKT3 were lower than the patients had low exosomal circAKT3. In conclusion, high circulating exosomal circAKT3 is associated with a higher risk of HCC recurrence and mortality. Follow-up of HCC patients with high exosomal circAKT3 after surgery may help to reduce the risk of recurrence and improve prognosis. Highlights: Circulating exosomal circAKT3 is significantly increased in HCC patients. High exosomal circAKT3 is associated with recurrence and mortality in HCC patients. HCC patients with high exosomal circAKT3 need more frequent postoperative monitoring.